Risk Factors and Diagnosis of Head and Neck Squamous Cell Carcinoma - Dewi, Yussy Afriani; Nazar, Ifiq; Farida, Anis (Faculty of Medicine, Universitas Padjadjaran, 2024)
Head and Neck Squamous Cell Carcinoma (HNSCC) ranks among the seven most prevalent malignancies globally, associated with significant morbidity and mortality rates. The key risk factors for this malignancy include chronic alcohol consumption, tobacco use, immunosuppression, and infections with oncogenic viruses such as high-risk Human Papillomavirus (HPV) and Epstein-Barr Virus (EBV). This study was a retrospective analysis of HNSCC patients seen at an oncology clinic over a five-year period from January 2015 to December 2020, focusing on the environmental and genetic factors contributing to the disease. A cohort of 1,640 patients was analyzed, assessing their risk factors and diagnostic outcomes. Results indicated that smoking and alcohol consumption were the most significant independent risk factors, displaying a synergistic effect in disease progression. Other variables explored were exposure to air pollution, HPV and EBV infections, age, dietary deficiencies in vegetables, and genetic predispositions. While some factors were statistically significant, others showed weaker associations. This study highlights the importance of preventive strategies focusing on modifiable risk factors, such as lifestyle changes and viral vaccination, to reduce the incidence of HNSCC.